CLOUD TECHNOLOGY: REVOLUTIONIZING MODERN SUPPLY CHAIN MANAGEMENT - Arjunkumar Vijayakumar (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
Cloud technology has fundamentally transformed supply chain management (SCM) by revolutionizing how organizations handle their operations, data management, and inter-organizational communications. This comprehensive article explores the technical foundations, implementation considerations, and future developments of cloud-based SCM systems. The article examines the architecture, security frameworks, and performance optimization strategies that enable organizations to achieve enhanced visibility, scalability, and operational efficiency. The article demonstrates how cloud-native technologies, real-time operational integration, and advanced security measures contribute to improved supply chain performance. Furthermore, it investigates the role of emerging technologies such as artificial intelligence, blockchain, and edge computing in shaping the future of supply chain operations.